Faktor Yang Memengaruhi Kinerja Tenaga Kesehatan Di Puskesmas Tangan-Tangan Kabupaten Aceh Barat Daya - Sulaiman Sulaiman; Ismail Efendy; Tri Niswati Utami (Jurnal Ventilator, 2024)
Resource management is very important to achieve organizational goals through management which is a tool to achieve these goals. The results of the initial survey found that the lack of discipline of officers due to not knowing and not understanding their responsibilities, this is because the responsibilities given are not in accordance with the educational background, the problem of low work motivation. The purpose of the study was to determine the factors that influence the performance of health workers at the Tangan-Tangan Health Center, Southwest Aceh Regency. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all health workers at the Tangan-Tangan Health Center as many as 75 people, all of whom were used as research samples. Data analysis with logistic regression. The results showed that there was an influence of leadership p = 0.000, motivation p = 0.000, discipline p = 0.000, incentives p = 0.002, work environment p = 0.000 and work ability p = 0.017 on the performance of health workers at the Tangan-Tangan Health Center, Southwest Aceh Regency. While the most dominant variable is discipline p = 0.003 and 95% CI = 6,862-11243,720 with an Exp (B) value = 277,759. The conclusion of this study is that there is an influence of leadership, motivation, discipline, incentives, work environment and work ability on the performance of health workers at the Tangan-Tangan Health Center, Southwest Aceh Regency. It is recommended to the leadership of the Puskesmas to always monitor the work of health workers in carrying out their duties, so that health workers can be monitored when carrying out their work and always provide opportunities to attend various trainings for health workers as an effort to develop themselves and be able to update their knowledge according to their expertise.